任务型教学法与对外汉语教学研究综述 - Ting, Hie Ling; Lam, Kai Chee (Confucius Institute Universitas Sebelas Maret, 2025)
The Task-based Language Teaching method (TBLT) which also known as Task-based Approach (TBA) or Task-based Instruction (TBI) was proposed by Prabhu. It became popular in the 1990s, which earned the title of